2022
DOI: 10.1038/s41467-022-28751-5
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of ocean circulation near the Dotson Ice Shelf, Antarctica

Abstract: Recent rapid thinning of West Antarctic ice shelves are believed to be caused by intrusions of warm deep water that induce basal melting and seaward meltwater export. This study uses data from three bottom-mounted mooring arrays to show seasonal variability and local forcing for the currents moving into and out of the Dotson ice shelf cavity. A southward flow of warm, salty water had maximum current velocities along the eastern channel slope, while northward outflows of freshened ice shelf meltwater spread at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 61 publications
(88 reference statements)
0
18
0
Order By: Relevance
“…Adusumilli et al (2020) used a wide range of remotely sensed surface elevations to obtain basal melt rates at quarter-yearly resolution but at the cost of the spatial resolution. Dotson Ice Shelf did not show noticeable changes in basal melt over the study period, however, ocean observations from the Dotson ice shelf cavity do show variations on seasonal timescales of inflow of warm circumpolar deep water (Jenkins et al, 2018;Yang et al, 2022). This could imply seasonal variability in the basal melt rates, as has been observed at both the Nivlisen Ice Shelf in East Antarctica (Lindbäck et al, 2019) and the Filchner-Ronne Ice Shelf (Vaňková and Nicholls, 2022).…”
Section: Discussionmentioning
confidence: 77%
“…Adusumilli et al (2020) used a wide range of remotely sensed surface elevations to obtain basal melt rates at quarter-yearly resolution but at the cost of the spatial resolution. Dotson Ice Shelf did not show noticeable changes in basal melt over the study period, however, ocean observations from the Dotson ice shelf cavity do show variations on seasonal timescales of inflow of warm circumpolar deep water (Jenkins et al, 2018;Yang et al, 2022). This could imply seasonal variability in the basal melt rates, as has been observed at both the Nivlisen Ice Shelf in East Antarctica (Lindbäck et al, 2019) and the Filchner-Ronne Ice Shelf (Vaňková and Nicholls, 2022).…”
Section: Discussionmentioning
confidence: 77%
“…Other processes, such as eddies (Daae et al., 2017; Foppert et al., 2019; Stewart & Thompson, 2015), Ekman pumping (Dotto et al., 2019; Kim et al., 2017), and circulation changes over the continental shelf (Daae et al., 2017; Darelius et al., 2016; Yang et al., 2022), are also of great importance to mCDW intrusions onto the continental shelf. These earlier studies showed that wind changes over the continental shelf play an important role in these processes and have a significant influence on the mCDW transport and water mass property changes over the continental shelf.…”
Section: Discussionmentioning
confidence: 99%
“…Yager et al, 2012). The intrusion of CDW into the Amundsen Shelf through the Dotson Trough provides the heat that accelerates ice melt (Jenkins et al, 2010; T. W. Yang et al, 2022). The mixing of CDW with overlying shelf waters forms mCDW (Jenkins et al, 2010;Miles et al, 2016).…”
Section: 1029/2022jg007053mentioning
confidence: 99%